Structural Health Monitoring of Helicopter Fuselage - Robert Hudec; Ladislav Janousek; Miroslav Benco; Pavol Makys; Vladimir Wieser; Martina Zachariasova; Matej Pacha; Vladimir Vavrus; Martin Vestenicky (Communications - Scientific letters of the University of Zilina, 2013)
The helicopter design is a challenging experience for fatigue concern as it is subjected to a very wide range of low- and high-frequency load cycles per flight, much more than a fixed wing aircraft. Structural Health Monitoring (SHM) seems to have capability in helping to reduce the maintenance and operational costs, which are about 25 percent of the direct operating cost of the helicopter, thus playing an important role especially in the case of the ageing helicopters. In fact, the damage tolerant design approach makes the fatigue resistance evaluation not only a safety issue but also a maintenance related concern. The work presented in this paper is a part of an international research project HECTOR (HElicopter fuselage Crack moniToring and prognosis through On-board sensoR network), founded by the European Defense Agency (EDA) and supported by 10 EDA Member States: Cyprus, France, Germany, Greece, Hungary, Italy, Poland, Slovakia, Slovenia and Spain.